Kebijakan Rusia untuk Bertahan Menghadapi Sanksi Ekonomi Uni-Eropa di Tahun 2016-2020 Melalui Strategi Import Substitution - Igo Ilham Mahendra (Pena Wimaya, 2022)
In the dynamics of Russia's relations with the European Union, at the beginning of the administration of President Vladimir Putin, Russia tried to approach the European Union as a trading partner. However, after Russia's intervention in Ukraine and the annexation of Crimea and the imposition of economic sanctions by the European Union on Russia in 2014, relations between the two entities became strained. Both parties impose sanctions on each other. Russia and the EU are two entities that have not much different influence and power. Therefore, this theme is important as an analysis of Russia's defense stance against the European Union Economic sanctions in 2016-2020 through the Import Substitution strategy. The author uses a national interest approach to analyze this problem. In this paper the author argues that the Import Substitution strategy is a form of policy to survive the economic sanctions of the European Union and as Russia's national interest over economic sovereignty.